Predicting Islamic Finance Adoption Behavior by MSMEs: Institutional Theory Approach - Usman, Usman; Kusuma, Hadri; Ardiansyah, Misnen (Universitas Muhammadiyah Yogyakarta, 2022)
Research aims: This study aims to develop and validate a prediction model for the Islamic finance adoption by MSMEs based on isomorphism theory. In addition, this study also intends to show that the individual cognitive theory approach employed by previous studies in this area is not appropriate.Design/Methodology/Approach: The research strived to develop a predictive model; therefore, variance-based SEM analysis was chosen. The research data were 242 MSMEs selected from four regencies/cities in Central Java Province, i.e., Semarang City, Pekalongan City, Jepara Regency, and Cilacap Regency. The analysis was carried out to ensure that the measurement and structural models were excellent and acceptable.Research findings: This study successfully constructed and validated a model to predict the behavior of adopting Islamic finance by MSMEs employing the isomorphism theory framework. The resulting model has considered a more comprehensive domain, i.e., external organization (isomorphism pressure), internal organization (good corporate governance, GCG), and individual characteristics of the leaders (halal self-awareness, HSA).Theoretical contribution/Originality: This study closed the research gap in investigating the determinants of Islamic finance adoption from the demand side using an organizational perspective, thereby contributing to building a body of knowledge in the domain of MSME behavior and Islamic finance. Theoretically, the resulting model can be an alternative or substitute for the previous approach. As an organization, MSME behavior should not be investigated using individual cognitive theory as done by all previous studies. This study also introduced a new construct called halal self-awareness (HSA). This construct can be exploited and further developed to investigate individual characteristics of halal products or concepts.Practitioner/Policy implication: Stakeholders must have a strong commitment and earnest efforts to increase coercive and mimetic pressures, increase the HSA of MSME owner-managers, and realize good MSME governance. All this will encourage MSMEs to adopt Islamic finance to contribute positively to improving the national Islamic economic and financial landscape.Research limitation/Implication: The HSA construct could not reveal its direct effect on the adoption behavior of MSMEs. Therefore, future studies need to pay more attention to the measures for the HSA construct, namely: HSA neutral (“I know exactly how well my awareness about…”) or HSA positive (“I know exactly that I have a good awareness of .... ”). That way, the impact of the HSA becomes more accurate.